THE PROVISION OF ENVIRONMENTAL BENEFITS BY SMALL FARMS FROM A REGIONAL PERSPECTIVE – SELECTED PROBLEMS - Agnieszka Ginter (Polityki Europejskie, Finanse i Marketing)
The changing model of functioning of agriculture brings new directions of its development, including functions related to providing environmental benefits. Environmental protection has become the most important point of reference in shaping all policies implemented by the European Union (EU), including the Common Agricultural Policy. Farmers, as its main beneficiaries, should take this into account. Decisions made by agricultural producers in their production processes are of great importance to the environment. The aim of the paper was to show and analyze regional differentiation of environmental benefits resulting from the functioning of small farms on the example of selected farm characteristics. The data for the analysis was obtained from the System of Collection and Use of Farm Accounting Data (Polish FADN) from three years (2017, 2018 and 2019). On the basis of a comparative and statistical analysis, it was concluded that the provision of environmental benefits by small farms is regionally differentiated. Soil protection and pro-environmental measures are emphasized in the Common Agricultural Policy's new arrangements for 2023-2027. This will primarily require knowledge transfer at the level of the institutional environment of agriculture (primarily of an advisory nature) at the national and regional level.